Seroepidemiological study of rotavirus infection in rural Ghana - Biritwum, R.B.; Isomura, S.; Yamaguchi, H.; Toba, M.; Mingle, J.A. (Annals of Tropical Paediatrics, 1984)
Children in a village in rural Ghana were found to have acquired antibody to rotavirus by the age of two years. The results of our study suggest that primary infection takes place early in infancy. Fifty-six per cent of the three- to 20-months-old had a four-fold rise in antibody levels during the six months follow-up period and 72.2% of them had one or more episodes of diarrhoea compared with 42.8% of those whose antibody levels stayed the same or decreased. The major epidemic season is considered to be the dry season.